Midnight city : a conquered Earth novel - Mitchell, J. Barton (Thomas Dunne Books/St. Martin's Griffin, 2013)
In a world where an alien race known as the Assembly has taken over Earth and humans are put in a subservient trance when they reach their early twenties, bounty hunter Holt Hawkins, treasure seeker Mira Toombs, and Zoey, a girl who has no memory, travel to Midnight City, meeting young freedom fighters, mutants, pirates, and aliens along the way, and realizing Zoey has powers which may be the key to overcoming the Assembly.